Pengaruh Profitabilitas , Ukuran Perusahaan Dan Dividend Payout Ratio Terhadap Perataan Laba Pada Sektor Consumer Cyclicals Di Indonesia - Mohamad Zulman Hakim; Rika Ristianti; Djenni Sasmita; Hamdani Hamdani; Hesty Erviani Zulaecha; Dewi Rachmania (Pusat Riset dan Inovasi Nasional, 2023)
This study used 10 Consumer Cyclicals companies listed on the IDX for 2018-2021 using the Purposive Sampling method to test company growth, profitability, company size and dividend payout ratio on earnings variance. Which in the analysis with panel data regression method. The results of this study indicate that company growth has no effect on income smoothing, company size has a negative effect on income smoothing, and the dividend payout ratio has no effect on income smoothing